Current Diagnostic and Therapeutic Approaches in May–Thurner Syndrome in Children, Adolescents, and Young Adults: A Survey among Thrombosis Experts of the German Society of Thrombosis and Haemostasis - Cuntz, Franziska; Gebauer, Bernhard; Greiner, Andreas; Hagedorn, Nikola; Reschke, Madlen; Eberl, Wolfgang; Zieger, Barbara; Lindhoff-Last, Edelgard; Holzhauer, Susanne (Hämostaseologie, 2024)
May–Thurner syndrome (MTS) is a pelvic venous disorder involving compression of the left common iliac vein by the right common iliac artery, which results in predisposition for deep vein thrombosis. Although MTS is increasingly recognized in young patients, specific guidelines on diagnosis and management for children, adolescents, and young adults do not exist so far. The aim of this study was to assess current diagnostic and therapeutic practice in Germany, Austria, and Switzerland in children and young adults with thrombosis and MTS.We designed an online survey with 11 questions, which we sent via a mailing list to all members of the German, Austrian, and Swiss Society of Thrombosis and Haemostasis Research. Between July and October 2022, 33 specialists answered the questionnaire. Most participating specialists worked at pediatric hospitals (61%). Numbers of annually treated thromboses ranged from <5 (26%) to >30 (13%). Most specialists used venous ultrasound to diagnose deep vein thrombosis, 53% magnetic resonance imaging. Only 25% of specialists systematically screened for MTS in deep vein thrombosis. MTS was managed with anticoagulation (65%), iliac vein stent placement (32%), or balloon angioplasty (13%). In total, 31% of specialists reported to use more than one therapeutic method. Diagnostic and therapeutic approaches for MTS differed between specialists. Lack of standardization resulted in individualized and highly diverse management. Prospective observational clinical studies investigating the outcome of different management strategies including long-term follow-up on outcome and incidence of postthrombotic syndrome will help in defining patient groups who benefit most from revascularizing interventional strategies and developing standardized guidelines.
Keywords: venous thrombosis; May–Thurner syndrome; iliac vein compression syndrome; children; adolescents; young adults